“I Really Feel Heard by AI”: A Cultural Case Study of AI-Mediated Listening Across China and the UK - Xin Zhan (Culture, Medicine, and Psychiatry, 2026)
Abstract The increasing use of generative AI for emotional support has prompted growing debate about the future of mental health care. This article suggests that such reliance is better understood not simply as a technological shift, but as symptomatic of a wider crisis in the politics of listening. This cultural case study examines the experiences of Lily, a 24-year-old Chinese migrant woman navigating emotional distress across uneven care infrastructures in China and the UK. Drawing on person-centred ethnography, it shows how AI chatbots come to function as provisional sites of care under conditions of precarity, gendered obligation, and moralised endurance. The analysis conceptualises these chatbot interactions as a care-patch : a temporary form of digital holding that emerges where human listening is scarce, delayed, or experienced as burdensome. Rather than treating AI use as a matter of technological adoption, the case situates AI-mediated listening within culturally specific moral relations of obligation and responsibility. In doing so, it reframes therapeutic automation as an index of the erosion of listening as a shared social good and redirects attention to the political and ethical challenge of rebuilding infrastructures of human listening capable of absorbing distress without extracting it, outsourcing it, or returning it as blame.